Development of a method for determining binaural sensitivity to temporal fine structure - Füllgrabe, Christian; Harland, Andrew J.; Sęk, Aleksander P.; Moore, Brian C.J. (Taylor & Francis, 2017)
Objective: To develop and evaluate a test of the ability to process binaural temporal-fine-structure (TFS) information. The test was intended to provide a graded measure of TFS sensitivity for all listeners. Design: Sensitivity to TFS was assessed at a sensation level of 30 dB using the established TFS-LF test at center frequencies of 250, 500, and 750 Hz, and using the new TFS-AF test, in which the interaural phase difference (IPD) was fixed and the frequency was adaptively varied. IPDs varied from 30 to 180°. Study Sample: Nine young (19-25 years) and 23 older (47-84 years) listeners with normal hearing over the tested frequency range. Results: For the young listeners, thresholds on the TFS-AF test did not improve significantly with repeated testing. The rank-ordering of performance across listeners was independent of the size of the IPD, and moderate-to-strong correlations were observed between scores for the TFS-LF and TFS-AF tests. Older listeners who were unable to complete the TFS-LF test were all able to complete the TFS-AF test. Conclusion: No practice effects and strong correlations with an established test of binaural TFS sensitivity make the TFS-AF test a good candidate for the assessment of supra-threshold binaural processing.